The Effect of Gochujang Immersion on Color Change and Surface Roughness of Nanofilled Resin Composite - Rosalina Tjandrawinata; Gavin Benedict Iskandar; Florencia Livia Kurniawan; Dewi Liliany Margaretta; Eddy Eddy; Aryadi Subrata (Sriwijaya Journal of Dentistry, 2025)
Background: Nanofilled resin composites are popular for their aesthetics but are vulnerable to discoloration and surface degradation, particularly in acidic environments. Gochujang, a Korean chili paste, is increasingly consumed and may affect dental restorations. Objectives: To evaluate the effect of gochujang sauce immersion on the color stability and surface roughness of nanofilled resin composite. Methods: Thirty-three Filtek™ Z350 XT A3 samples were divided into three groups (n=11): immediate control, distilled water control, and gochujang treatment. The treatment group was immersed daily in a 1:1 gochujang-distilled water solution (16 h) and distilled water (8 h) for four days at 37°C. Color change (ΔE) was measured with a VITA Easyshade V spectrophotometer; surface roughness (Ra) with a Taylor Hobson Surtonic S-100. Results: Gochujang immersion significantly increased color change (ΔE, p<0.001) and surface roughness (Ra, p=0.009) compared to controls between groups (p<0.05). Conclusion: Gochujang immersion adversely affects both color stability and surface roughness of nanofilled resin composites.